2018
DOI: 10.21037/qims.2018.05.06
|View full text |Cite
|
Sign up to set email alerts
|

Review of radiological screening programmes for breast, lung and pancreatic malignancy

Abstract: The premise of medical screening is to identify clinically occult disease, facilitating intervention at an early stage with the intention of improving prognosis. Identifying solid organ malignancy before nodal or distal metastases have occurred unanimously offers the best chance of successful radical treatment, thus there is clearly a potential significant mortality benefit for successful oncological screening programmes. However, the negative consequences of screening have to be considered, particularly the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In women, breast cancer is the most common disease in incidence (2.1 million new cases in 2018) and mortality (627,000 deaths in 2018) when compared to all cancers [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In women, breast cancer is the most common disease in incidence (2.1 million new cases in 2018) and mortality (627,000 deaths in 2018) when compared to all cancers [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the wide application of high-resolution CT and the established role of low-dose helical computed tomography (CT) screening for lung cancer, pulmonary lesions are increasingly detected (1,2). Image-guided biopsy is still required for lesions that cannot be determined by CT or malignant lesions diagnosed by CT need to be clarified histopathologically or genetic types before radiotherapy or chemotherapy (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…It has the highest rate of incidence and mortality in China (2). Low-dose computed tomography (LDCT) is the most widely used modality for early lung cancer detection and mortality reduction (3,4). Research has shown that among LDCT screening participants, the prevalence of small solid pulmonary nodules (SSPNs) was higher than that of non-solid nodules (NSNs) and part-solid nodules (PSNs), while other studies have demonstrated that malignancy is most frequently detected in SSPNs larger than 6 mm (5,6).…”
Section: Introductionmentioning
confidence: 99%